Business Model Canvas: Car Top Brush / Nur Umairah Tumiran - Tumiran, Nur Umairah (2020)
From the previous report of New Product Development, I have shown the new product that have been designed which called ‘Car Top Brush’. After that, I will do the Business Model Canvas (BMC) to introduce participants an entrepreneurial tool for the construction of a basic business plan. Also, to provide transferable knowledge and skills such as hands on experience using the tool, oral communication, critical analysis and team-work. The Business Model Canvas (BMC) is a strategic management and entrepreneurial tool that allows you to describe, design, challenge, invent, and capture values. From the model, I can create a new business models easily and also analyse and update the existing business models. There are 9 blocks in the Business Model Canvas (BMC) which are customer segment, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships and cost structure. In this report, I will explain each of the blocks in detail